Analisis Bisphenol A Dan Di-Ethylhexyl Phthalate dalam Air Galon yang Beredar di Kota Makassar - Endah Dwijayanti; Rachim Munadi; Sry Wahyuningsih; Iffana Dani Maulida (LPPM Universitas Terbuka, 2023)
Bisphenol A (BPA) and Di-Ethylhexyl Phthalate (DEHP) are chemical compounds that are used as raw materials for making disposable bottles or PET, including gallons. BPA can migrate into food or drink if the temperature is raised due to heating processes. This research aimed to identify BPA and DEHP compounds in various brands of gallon water distributed in Makassar and the effect of sun exposure towards BPA and DEHP migration. The sampling method was done based on an early analysis from field survey data in the location that represents all gallon water refills distributed in Makassar. There were 4 selected samples from 2 most marketed brands of gallon water refill. Research method included sample preparation with two different treatments, namely with exposure and without exposure to sunlight by letting them settle inside and outside the room for 6 days, afterwards, BPA and DEHP were analyzed using Gas Chromatography - Mass Spectrometry (GC-MS). The results of the study show that in various brands gallon water packages, both with sun exposure or without, no BPA and DEHP compounds were detected.